Electrocatalytic and Solar‐Driven CO2 Reduction to CO with a Molecular Manganese Catalyst Immobilized on Mesoporous TiO2. Issue 26 (25th April 2016) - Rosser, Timothy E.; Windle, Christopher D.; Reisner, Erwin
Abstract: Electrocatalytic CO2 reduction to CO was achieved with a novel Mn complex, fac ‐[MnBr(4, 4′‐bis(phosphonic acid)‐2, 2′‐bipyridine)(CO)3 ] (MnP ), immobilized on a mesoporous TiO2 electrode. A benchmark turnover number of 112±17 was attained with these TiO2 |MnP electrodes after 2 h electrolysis. Post‐catalysis IR spectroscopy demonstrated that the molecular structure of theMnP catalyst was retained. UV/vis spectroscopy confirmed that an active Mn–Mn dimer was formed during catalysis on the TiO2 electrode, showing the dynamic formation of a catalytically active dimer on an electrode surface. Finally, we combined the light‐protected TiO2 |MnP cathode with a CdS‐sensitized photoanode to enable solar‐light‐driven CO2 reduction with the light‐sensitiveMnP catalyst. Abstract : One small step for Mn : A Mn catalyst immobilized on TiO2 gave electrocatalytic CO2 reduction with a turnover number of 112. The low overpotential of 420 mV is a result of dimerization of the catalyst on the mesoporous electrode. The heterogeneous hybrid cathode was used in a photoelectrochemical cell enabling solar‐driven CO production by a photo‐unstable Mn catalyst for the first time.